Strengthening the MSME Digital Economy as Indonesia's National Economic Resilience - Badri, Ferdian; Amrina, Dania Hellin (AIBPM Publisher, 2023)
The objective of this research is to examine policies that enhance national economic resilience by leveraging the digital economy for Micro, Small, and Medium Enterprises (MSMEs). The employed methodology involves a descriptive approach through a literature review utilizing PESTEL analysis (Politics/Policy, Economic, Social, Technology, Education, and Legal). PESTEL analysis results show positive results for several factors, namely Politics/Policy and Economics, meaning that these factors contribute to the advancement of the digital economy in Indonesia, encompassing Sosial, Technologial, Legal, and Educational asects. There are still gaps and inadequate regulations for the community and MSME actors.